ELSA: A Mobile Application With Artificial Intelligence To Enhance Students' English Vocabulary and Pronunciation - Yosefina Elsiana Suhartini; Bonifasius Berdi; Yohanes Tresno Kurnianto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to investigate the effect of using the ELSA application designed with artificial intelligence on students' English vocabulary mastery and pronunciation skills. The research method used was a quantitative approach with a quasi-experimental design. The study involved population and sample selection, data collection instruments such as tests and observations, as well as data analysis techniques including validity test, reliability, normality test, homogeneity test, hypothesis testing, and effect size calculation. The results showed that the experimental group using the ELSA application had a higher average score compared to the control group. Statistical analysis showed a significant difference between the scores of the experimental group and the control group, with a strong effect of the ELSA application on students' skills. Furthermore, when utilizing the ELSA application to learn English, students appear pleased, energetic, and very excited. Therefore, it can be concluded that the ELSA application effectively improves students' English vocabulary and pronunciation skills.